Analysis of the Influence of Savings and Loans Products and Service Quality on Loyalty and the Role of Satisfaction as a Moderation Variable - Koidatul Nurulaeni; Wahju Wulandari; Nasharuddin Mas (Optima Science, 2024)
The purpose of this research is to determine the effect of savings and loan products and service quality on customer loyalty which is moderated by customer satisfaction in the study of KPRI Yustisia customers at the Malang District Court. The sampling technique in this research uses